Climate smart village project in Vaishali, Bihar in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
This photoset contains pictures taken in relation to climate smart villlage-activities in South Asia. in India, Vaishali. Photo : V.Reddy (ViDocs)